The Impact of Using Skimming Strategy in Narrative Text towards Students’ Reading Comprehension of SMP Advent of Semarang - Aprilia Rosmarie; Mualimin Mualimin (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
Reading is one of the four English skills that is important in academic and daily life. Many strategies can be used in reading, such as skimming, scanning, summarizing and responding, and note taking. The purposes of this research are to investigate the significant improvement of the students’ skills after using skimming strategy in reading narrative text and students’ responses after using this strategy. The researcher investigated 8th graders of SMP Advent of Semarang who were studying narrative text. The data were analysed in quantitative and qualitative methods. The results showed that there was a significant improvement of the students after using skimming strategy, especially comprehending the narrative text. The result indicated that p-value = 0,019588. Therefore, null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. Their score increased and it proved that skimming strategy is useful and help the students enhance students’ reading skills.